ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI FINANCIAL DISTRESS (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2014 â 2016) - Elsa Yuda Pratiwi, 14.05.52.0210; Badjuri, Achmad (Students Journal of Accounting and Banking, 2018)
This study aims to examine and analyze the effects of liqudity, leverage, profitability, sales growth company size, institutional ownership, managerial ownership of financial distress on manufacturing companies listed on BEI period 2014-2016. The population in this study is all manufacturing companies registered in BEI period 2014-2016. The sample selection using purposive sampling method. The analysis tool used in this research is logistic regression analysis. The results of the research show that Leverage influence has Positive significant of financial distress. Profitability and Sales Growth have significant negative effect on financial distress, while Liquidity, Company Size, Institutional Ownership, Managerial Ownership have no significant effect on financial distress.Keywords: Financial Distress, Liquidity, Leverage, Profitability, Sales Growth, Company Size, Institutional Ownership, and Managerial Ownership